Risk spatial distribution and economic loss assessment for parallel reservoir group dam-break floods: A case study of southwest river basin in China - Jinjun Zhou; Chunxin Sun; Jiahong Liu; Ruirui Sun; Songyun Jin; Chenrui Qin; Hao Wang (Journal of Hydrology: Regional Studies)
Study region: Zhaotong City, located in the Jinsha River Watershed in southwest China, features a developed river network, mountainous terrain, and significant elevation changes. The region experiences a low-latitude plateau monsoon climate, with rainfall concentrated in the wet season. Study focus: This study uses a 2D hydrodynamic model and a dam-break flood model to assess flood risks of parallel reservoirs and quantify direct economic losses under different scenarios. It also explores the causes of risk and loss variations across scenarios. New hydrological insights for the region: Differences in dam site locations and downstream topography result in significant variations in inundation areas, with extreme cases differing by nearly twofold. Dam-break flood losses depend on inundation extent, water depth, and land value. Variations in high-value land inundation, such as residential, commercial, and industrial areas, are the main reason for differences in direct economic losses. The fatality area of a dam-break flood from parallel reservoirs is smaller than the sum of individual reservoirs due to river confluence effects, delaying the flood's arrival at the city center. Overall, parallel reservoir dam-break risks are influenced by multiple factors, requiring case-specific analysis rather than simple risk summation.